Synthesis Of Derivate Acetophenone From Fenol And Eugenol - Kapelle, Imanuel B. D.; Matsjeh, Sabirin (Indonesian Journal of Chemical Research, 2013)
The synthesis derivate acetophenone from fenol and eugenol had been carried out. The acylation of fenol was performed by anhydride acetate and the fries rearrangement reaction was carried out using AlCl3 catalyst at temperature of 50oC produce ortho-hydroxyacetophenone (35,29 %), purity was tested by GC, structure elucidation of these product ware analized by FTIR and 1H-NMR. Acylation reaction of eugenol was performed by anhydride acetate in base condition at temperature of 120oC for 3 h produce 5-allyl-2-hydroxy-3-metoksi acetophenone (21,42%), purity was tested by GC, structure elucidation of these product ware analized by FTIR, 1H-NMR and MS.